The Influence of the Application of Islamic Values in the World of Work on the Work Ethic and Productivity of Employees in Pelindo Regional 3 - Prawirosastro, Carlos Lazaro; Saputra, Toto Dwijaya (Majapahit Journal of Islamic Finance and Management, 2025)
Employee productivity is one of the most crucial indicators of organisational performance in the modern era, including in the port sector, which is full of challenges and operational complexity. Islamic values such as ihsan (spiritual professionalism), honesty, and trustworthiness have an important role in shaping a strong work ethic. This study aims to analyse the effect of the application of Islamic values on work ethic and employee productivity, and to examine the mediating role of work ethic. This research uses a quantitative approach with an explanatory design and a causal-comparative research type. The sampling technique is total sampling, namely all 34 employees of Pelindo Regional 3 were used as samples. Data were collected using a questionnaire with a 5-point Likert scale. Data were analyzed using a Structural Equation Modeling approach based on Partial Least Squares (PLS-SEM). The results showed that Islamic values have a significant effect on employee work ethic (p-value 0.000, t-statistic 6.421), and have a significant effect on work productivity both directly (p-value 0.043, t-statistic 2.028) and indirectly through the mediation of work ethic (p-value 0.000, t-statistic 3.431). Work ethic has a significant effect on productivity (p-value 0.015, t-statistic 2.503). The R-Square value for the work ethic is 0.389, and for work productivity is 0.404 (fairly strong model contribution). These findings suggest that the integration of Islamic values can be an important foundation in improving the quality of human resources. Organisations need to embed spiritual values in the work culture through training, coaching, and the leader's example.